Pope John Paul II's theology of work - Włodzimierz Wieczorek (The Francis de Sales Scientific Society (TNFS.PL), 2023)
The human being is in the center of John Paul II's vision of work. There is no work without the human being. The personalistic attitude to work is in line with the ethics of work, because labor or capital must contribute to the good of humanity. The ethics of work highlights the value attached to the worker. The theology of work cannot exist without recognizing the subjective dimension of work. The ethics of work is centered on man because of his and his fellow men's good, and thus saves the worker from being disconnected from work. Work that is devoid of moral sense becomes pointless, as it loses its social meaning and becomes a source of socioeconomic problems.